2020
DOI: 10.2147/ptt.s272286
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation Between Psoriasis Severity and Nonalcoholic Fatty Liver Disease Degree Measured Using Controlled Attenuation Parameter</p>

Abstract: Background: A growing body of evidence links psoriasis to several metabolic disorders, but the causal relationship between psoriasis and nonalcoholic fatty liver disease (NAFLD) remains understudied. Purpose: To measure the correlation between the severity of psoriasis and the degree of NAFLD. Patients and Methods: A cross-sectional study was conducted on adult patients with psoriasis in the Dermatovenereology Outpatient Clinic of Cipto Mangunkusumo Hospital from December 2017 through February 2018. Psoriasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…These signals pass between these three organs, configuring an hepato-dermal axis [ 42 ]. Moreover, these processes, that involve chronic mild systemic inflammation and insulin resistance, are also thought to mediate the association between the severity of psoriasis and MAFLD [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…These signals pass between these three organs, configuring an hepato-dermal axis [ 42 ]. Moreover, these processes, that involve chronic mild systemic inflammation and insulin resistance, are also thought to mediate the association between the severity of psoriasis and MAFLD [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…TSA showed that the analysis of OR included sufficient cases and there was a publication bias across the studies for the calculation of pooled ER and OR. [34] Turkey Caucasian 20/250 -44 MSP US, liver test, exclusion of other liver diseases Fahim, 2023 [35] Pakistan Asian 30/80 16/80 38 CPP US, liver test, exclusion of other liver diseases Ruan, 2022 [39] China Asian 96/148 4018/5524 38.8 NR US, liver test, exclusion of other liver diseases Ghafoor, 2021 [12] Pakistan Asian 53/101 29/101 46.4 NR US, liver test, exclusion of other liver diseases Gau, 2022 [36] China Asian 1191/5591 295,749/1,479,360 50.4 NR US, liver test, exclusion of other liver diseases Inci, 2016 [37] Turkey Caucasian 32/60 21/60 44.5 CPP US, liver test, exclusion of other liver diseases Lee, 2019 [38] China Asian 34/307 ->18 NR Not described Valenzuela, 2022 [40] Chile Mixed 28/598 -49.2 Mixed Not described Gandha, 2020 [41] Indonesia Asian 28/36 -40.1 Vulgaris US, liver test, exclusion of other liver diseases Shibata, 2022 [46] Japan Asian 13/46 14/138 50.6 Mixed US, liver test, exclusion of other liver diseases Li, 2022 [44] China Asian 46/127 -46.5 PsA US, liver test, exclusion of other liver diseases Yadav, 2023 [47] India Asian 17/50 2/50 38.9 CPP US, liver test, exclusion of other liver diseases Ho, 2019 [43] China Asian 58/223 -58 PsA US, liver test, exclusion of other liver diseases Ortolan, 2019 [45] Italy Caucasian 40/76 -57.7 PsA US, liver test, exclusion of other liver diseases Gisondi, 2016 [42] Italy Caucasian 55/124 21/79 55 CPP US, liver test, exclusion of other liver diseases Gisondi, 2009 [13] Italy [51] China Asian 34/307 ->18 NR Not described Magdaleno-Tapial, 2020 [52] Spain [58] India Asian 17/61 5/24 46 CPP US, liver test, exclus8ion of other liver diseases…”
Section: Discussionmentioning
confidence: 99%
“…[23,70] Psoriasis is an immune-mediated inflammatory skin disease and chronic inflammation, a common feature of both psoriasis and NAFLD, plays a crucial role in the development and progression of these conditions. [41] Certain cytokines, such as interleukin-22, interleukin-17, and tumor necrosis factor-alpha, are known to be involved in the development of psoriasis and these cytokines also contribute to insulin resistance, which is associated with NAFLD development. [41,[71][72][73][74] Metabolic disorders cause both psoriasis and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Most common inflammatory pathways in MAFLD and other immune-mediated diseases depend on the establishment of systemic inflammation. Several epidemiological studies confirmed an increased prevalence of MAFLD in patients with psoriasis, accounting for double the risk of patients without this disease ( 93 ), and increasing the extension of psoriasis lesions ( 94 ). Psoriasis is a chronic, systemic immune-mediated disease characterized by the development of erythematous, indurated, pruritic plaques in the skin ( 95 ).…”
Section: Immune-mediated Diseases and Mafldmentioning
confidence: 93%